Functional analysis of the beta and epsilon lycopene cyclase enzymes of Arabidopsis reveals a mechanism for control of cyclic carotenoid formation. - Cunningham, F X (1996)
Carotenoids with cyclic end groups are essential components of the photosynthetic membranes in all plants, algae, and cyanobacteria. These lipid-soluble compounds protect against photooxidation, harvest light for photosynthesis, and dissipate excess light energy absorbed by the antenna pigments. The cyclization of lycopene (psi, psi-carotene) is a key branch point in the pathway of carotenoid biosynthesis. Two types of cyclic end groups are found in higher plant carotenoids: the beta and epsilon rings. Carotenoids with two beta rings are ubiquitous, and those with one beta and one epsilon ring are common; however, carotenoids with two epsilon rings are rare. We have identified and sequenced cDNAs that encode the enzymes catalyzing the formation of these two rings in Arabidopsis. These beta and epsilon cyclases are encoded by related, single-copy genes, and both enzymes use the linear, symmetrical lycopene as a substrate. However, the epsilon cyclase adds only one ring, forming the monocyclic delta-carotene (epsilon, psi-carotene), whereas the beta cyclase introduces a ring at both ends of lycopene to form the bicyclic beta-carotene (beta, beta-carotene). When combined, the beta and epsilon cyclases convert lycopene to alpha-carotene (beta, epsilon-carotene), a carotenoid with one beta and one epsilon ring. The inability of the epsilon cyclase to catalyze the introduction of a second epsilon ring reveals the mechanism by which production and proportions of beta,beta- and beta, epsilon-carotenoids may be controlled and adjusted in plants and algae, while avoiding the formation of the inappropriate epsilon,epsilon-carotenoids.